2018
DOI: 10.1136/lupus-2018-000279
|View full text |Cite|
|
Sign up to set email alerts
|

Patient-reported outcome measures for use in clinical trials of SLE: a review

Abstract: Inclusion of patient-reported outcomes is important in SLE clinical trials as they allow capture of the benefits of a proposed intervention in areas deemed pertinent by patients. We aimed to compare the measurement properties of health-related quality of life (HRQoL) measures used in adults with SLE and to evaluate their responsiveness to interventions in randomised controlled trials (RCTs). A systematic review was undertaken using full original papers in English identified from three databases: MEDLINE, EMBAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 80 publications
2
31
0
Order By: Relevance
“…We found that PROMIS10 was not sensitive to changes in physicianassessed SLE disease activity. Similar findings have been shown in other disease specific and universal patient-reported outcome measures used in patients with SLE (21,22). We suspect that the difference in performance of the anchors reflects the different latent variables measured by patient-reported outcome surveys and physician-evaluated disease activity instruments.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We found that PROMIS10 was not sensitive to changes in physicianassessed SLE disease activity. Similar findings have been shown in other disease specific and universal patient-reported outcome measures used in patients with SLE (21,22). We suspect that the difference in performance of the anchors reflects the different latent variables measured by patient-reported outcome surveys and physician-evaluated disease activity instruments.…”
Section: Discussionsupporting
confidence: 82%
“…Few studies have examined the responsiveness of patientreported outcome measures to patient-reported changes in SLE. A study of 101 SLE patients in the UK who were followed at 4-week intervals for 10 months, found small to moderate effect sizes (-0.11 to 0.53) for deterioration and improvement of patient-reported health status in physical function and mental health domains of the SF-36 and the LupusQoL, a disease-specific patient-reported outcome measure (21). Similarly, a study of 185 French patients with SLE who completed up to 3 surveys 3 months apart found low to moderate sensitivity to change using a patient-derived global assessment of disease impact for both the SF-36 PCS and MCS (SRM -0.25 to -0.61) and related domains of the LupusQoL (25).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in 2018, Izadi et al reviewed the literature to assess the responsiveness of different PROs to interventions in RCTs. This review confirmed that SF-36 and LupusQoL have strong evidence for adequate psychometric measurement properties 58. In addition, the LIT and Patient-Reported Outcomes Measurement Information System (PROMIS) showed strong evidence for measurement properties; however, PROMIS responsiveness has not been studied in lupus, nor have LupusPRO or LIT been assessed in RCTs.…”
Section: Discussionmentioning
confidence: 58%
“…The primary outcomes were changes between baseline and week 16 in 11 domains reflecting various aspects of HRQoL, as assessed by 3 validated patient-reported outcome measures (PROMs): (1) Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F), consisting of 13 questions aggregated into 1 domain measuring fatigue; (2) Brief Pain Inventory-Short Form (BPI-SF), consisting of 15 questions classified into 2 domains (pain severity and pain interference), and; (3) Lupus Quality of Life (LupusQoL), consisting of 34 questions classified into 8 domains (fatigue, physical health, planning, burden to others, emotional health, pain, intimate relationships, and body image). All 3 outcome measures have been previously described [ 32 - 34 ] and validated for use in SLE [ 29 , 35 , 36 ]. The participants were asked to complete these PROMs on a secure website prior to the start of the intervention and at weeks 4, 8, 12, and 16.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to the study, the sample size was computed based on the Mann–Whitney U test to provide approximately 80% power to detect an effect size proportional to a mean difference in improvement of about 10% with a standard deviation of 10% without correcting for multiple comparisons. This effect size was chosen based on early user experience with the program as well as consideration of previously established minimally important differences for the outcome measures [ 35 - 37 ]. It was determined that a sample size of 50 was sufficient to allow for attrition and still produce the needed power with the remaining participants expected to complete the study.…”
Section: Methodsmentioning
confidence: 99%